Financial Innovation Drives Small Businesses - Spagnoletto, Paolo (World Bank, Washington, DC, 2012)
International Finance Corporation (IFC) makes selective investments in small businesses that are in frontier countries and have a strong developmental role. Since 2002, the corporation has made 25 or so small direct investments (SDI), most of which turned out to be success stories. Over the years, SDI developed a specific methodology that works well with small companies. But the most successful stories arise from innovative financial solutions tailored to help small businesses as they incubate and eventually graduate into fully bankable companies.